GE_GERICHTE A/4021/2021 vom 23. November 2023 - GE Cour de justice (2023)
Recours au TF formé le 12.12.2023 par la débitrice, rejeté par arrête du 20 mars 2024 (( | LP.221; LP.228; OAOF.29; OAOF.30; LP.222; LP.229; LP.244; LP.245; LP.207; LP.17; OAOF.63; LP.250